2004
DOI: 10.1590/s0100-204x2004000400008
|View full text |Cite
|
Sign up to set email alerts
|

Eficiência de fungos ectomicorrízicos na absorção de fósforo e na promoção do crescimento de eucalipto

Abstract: Resumo -O potencial de fungos ectomicorrízicos na promoção do crescimento das plantas e o controle da micorrização podem alavancar a exploração comercial desses fungos. O objetivo deste trabalho foi avaliar a eficiência de isolados de fungos ectomicorrízicos na colonização radicular, absorção de P e no crescimento de mudas de Eucalyptus dunnii, sob diferentes doses de fósforo. O inóculo dos isolados fúngicos INRA-Cou (Paxillus involutus), UFSC-Hg93 (Hysterangium gardneri), UFSC-Pt116 (Pisolithus microcarpus) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
1
11

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 11 publications
4
13
1
11
Order By: Relevance
“…The increase in eucalypt CD, SH, and SDM promoted by inoculation with increasing application rates of different EMF species (Figures 1a, 1b, 1c) was also observed by other authors in eucalypt seedlings (Alves et al, 2001;Souza et al, 2004Souza et al, , 2008. E. dunnii seedlings had greater CD (1.4 times), SH (1.3 times), and SDM (1.7 times) levels when inoculated with Pisolithus sp.…”
Section: Inoculation Effectsupporting
confidence: 83%
See 4 more Smart Citations
“…The increase in eucalypt CD, SH, and SDM promoted by inoculation with increasing application rates of different EMF species (Figures 1a, 1b, 1c) was also observed by other authors in eucalypt seedlings (Alves et al, 2001;Souza et al, 2004Souza et al, , 2008. E. dunnii seedlings had greater CD (1.4 times), SH (1.3 times), and SDM (1.7 times) levels when inoculated with Pisolithus sp.…”
Section: Inoculation Effectsupporting
confidence: 83%
“…Ectomycorrhizal fungi species differed in their capacity to increase leaf P concentration and content ( Figures 2a, 2b); however, they did not differ in terms of growth promotion (Figures 1a, 1b, 1c) and root colonization ability (Figure 1d), and they also raised leaf K and N concentration and content (Figures 2c, 2d, 2e, 2f). This similar behavior among EMF species observed in growth promotion, root colonization, and plant nutrition for some nutrients differs from most studies found in the literature (Alves et al, 2001;Silva et al, 2003;Souza et al, 2004Souza et al, , 2008Chen et al, 2006c).…”
Section: Inoculation Effectsupporting
confidence: 49%
See 3 more Smart Citations